An Updated Coverage on the Synthesis of Benzo[b]thiophenes via Transition-metalcatalyzed Reactions: A Review - Ejaz, Saba; Zubair, Muhammad; Rizwan, Komal; Karakaya, Idris; Rasheed, Tahir; Rasool, Nasir (Current Organic Chemistry, 2021)
The benzo[b]thiophene nucleus is ubiquitous in biologically and pharmaceutically important compounds. These moieties are highly important in materials science. The synthesis of benzothiophene as a privileged structure has readily become a subject of great interest and actively pursued in recent years. This review focuses on facile and convenient methods of synthesis of benzo[b]thiophene based molecules through different transition metals catalyzed reactions.
Keywords: heterocyclics